The Function of Love in Solzhenitsyn's The First Circle - John Schillinger (Studies in 20th & 21st Century Literature, 1977)
Aleksander Solzhenitsyn, like Boris Pasternak before him, insists upon the primacy of life over any socio-political system. To lead truly meaningful lives, his characters must comprehend that they are responsible for their own actions; that they are engaged in an existential struggle which pits individual freedom against the will of authority. In The First Circle, this struggle is clearly reflected in the theme of love which, when analyzed in terms of the suppression or triumph of its four basic elements (sex, eros, philia, and agape), offers a convincing allegory of man's existential self-definition by free choice.
Keywords: Aleksander Solzhenitsyn; love; The First Circle